Comparative effectiveness of triple therapy versus dual bronchodilation in COPD. Issue 3 (30th August 2019) - Voorham, Jaco; Corradi, Massimo; Papi, Alberto; Vogelmeier, Claus F.; Singh, Dave; Fabbri, Leonardo M.; Kerkhof, Marjan; Kocks, Janwillem H.; Carter, Victoria; Price, David
This real-world study compared the effectiveness of triple therapy (TT; long-acting muscarinic antagonists (LAMAs)/long-acting inhaled β-agonists (LABAs)/inhaled corticosteroids (ICSs)) versus dual bronchodilation (DB; LAMAs/LABAs) among patients with frequently exacerbating COPD. A matched historical cohort study was conducted using United Kingdom primary care data. Patients with COPD aged ≥40 years with a history of smoking were included if they initiated TT or DB from no maintenance/LAMA therapy and had two or more exacerbations in the preceding year. The primary outcome was time to first COPD exacerbation. Secondary outcomes included time to treatment failure, first acute respiratory event, and first acute oral corticosteroid (OCS) course. Potential treatment effect modifiers were investigated. In 1647 matched patients, initiation of TT reduced exacerbation risk (adjusted hazard ratio (HR) 0.87, 95% CI 0.76–0.99), risk of acute respiratory event (HR 0.74, 95% CI 0.66–0.84) and treatment failure (HR 0.83, 95% CI 0.73–0.95) compared with DB. Risk reduction for acute respiratory events was greater for patients with higher rates of previous exacerbations. At baseline blood eosinophil counts (BECs) ≥ 0.35×10 9  cells·L −1, TT was associated with lower risk of OCS prescriptions than DB. This study provides real-life evidence of TT being more effective in reducing exacerbation risk than DB, which became more accentuated with increasing BEC and previous exacerbation rate. In a real-world population of COPD patients with history of exacerbations, initiation of triple therapy was associated with a larger reduction in future risk of exacerbation, acute respiratory event, and treatment failure compared with dual bronchodilation http://bit.ly/2xA1Xut